Development of Novel Cardiac Indices and Assessment of Factors Affecting Cardiac Activity in a Bivalve Mollusc Chlamys farreri - Xing, Qiang; Zhang, Lingling; Li, Yuqiang; Zhu, Xinghai; Li, Yangping; Guo, Haobing; Bao, Zhenmin; Wang, Shi (Frontiers in Physiology, 2019)
Cardiac activity has been widely used in marine molluscs as an indicator for their physiological status in response to environmental changes, which is, however, largely less studied in scallops. Here, we monitored cardiac performance of Zhikong scallop Chlamys farreri using an infrared-based method, and evaluated the effects of several biotic (shell height, total weight, and age) and environmental factors (circadian rhythm and temperature) on scallop heart rate (HR), amplitude (HA), and rate-amplitude product (RAP). Results revealed that size has a significant effect on both HR (negative) and HA (positive), but RAP values are similar in different sized scallops. Age also affects scallop cardiac performance, significantly for HR, but not for HA or RAP. Circadian rhythm affects cardiac activity, with significant elevation of HR, HA and RAP during 1:00–8:00 and 17:00–19:00. With seawater temperature elevation, HR peaks at 30.03 ± 0.23°C, HA at 15.08 ± 0.02°C, and RAP at 15.10 ± 0.19 and 30.12 ± 0.28°C. This suggests HR is a good indicator for thermal limit, whereas HA may indicate optimal growth temperature, and RAP could be an index of myocardial oxygen consumption to indicate myocardium stress. Our study provides basic information on the factors that may affect scallop cardiac performance. It also elucidates the feasibility of HA and RAP as cardiac indices in marine molluscs.